2016
DOI: 10.1515/raon-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in glioblastoma: methyl guanine methyl transferase (MGMT) promoter methylation as independent favourable prognostic factor

Abstract: BackgroundIn spite of significant improvement after multi-modality treatment, prognosis of most patients with glioblastoma remains poor. Standard clinical prognostic factors (age, gender, extent of surgery and performance status) do not clearly predict long-term survival. The aim of this case-control study was to evaluate immuno-histochemical and genetic characteristics of the tumour as additional prognostic factors in glioblastoma.Patients and methodsLong-term survivor group were 40 patients with glioblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 48 publications
5
36
0
Order By: Relevance
“…Nowadays, standard treatment for high‐grade glioma is surgical resection followed by chemotherapy and irradiation, but clinical prognosis is still poor in patients with high‐grade glioma because of their aggressive capacity for proliferation and migration . Recent studies have provided us an increased knowledge on a number of molecular markers and/or gene mutations specific to human glioma, including the isocitrate dehydrogenase gene ( IDH1 ) mutation and methyl guanine methyl transferase promoter methylation, but have not yet led to the breakthrough of innovative therapeutic strategies for patients with gliomas …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, standard treatment for high‐grade glioma is surgical resection followed by chemotherapy and irradiation, but clinical prognosis is still poor in patients with high‐grade glioma because of their aggressive capacity for proliferation and migration . Recent studies have provided us an increased knowledge on a number of molecular markers and/or gene mutations specific to human glioma, including the isocitrate dehydrogenase gene ( IDH1 ) mutation and methyl guanine methyl transferase promoter methylation, but have not yet led to the breakthrough of innovative therapeutic strategies for patients with gliomas …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent studies have provided us an increased knowledge on a number of molecular markers and/or gene mutations specific to human glioma, including the isocitrate dehydrogenase gene (IDH1) mutation and methyl guanine methyl transferase promoter methylation, but have not yet led to the breakthrough of innovative therapeutic strategies for patients with gliomas. 3 On the other hand, recent studies strongly suggest that T-lymphokine-activated killer (T-LAK) cell-originating protein kinase (TOPK) may play master roles in tumorigenesis in various types of cancer, being a molecular target for malignant tumors. TOPK is a 322-amino acid serine-threonine kinase.…”
Section: Introductionmentioning
confidence: 99%
“…The survival outcomes of patients with a high-grade glioma are often poor and require significant improvement (1). A certain prolongation of the median survival time has already been achieved with the introduction of multi-modality treatment programs involving neurosurgery, radiation oncology and administration of systemic agents (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MGMT promoter methylation is a significant independent prognostic factor 37 and is more common among long-term survivors 30,38 . Despite having a relatively small sample of patients with known MGMT methylation status, our analysis was able to confirm that, for both males and females, MGMT methylation was more common among extreme survivors and was a significant independent prognostic factor.…”
Section: Impact Of Categorical Variables On Survivalmentioning
confidence: 99%
“…Methylation of the MGMT promoter has been found to be more common in long-term survivors 30 , so we also assessed the impact of MGMT methylation on the survival of our population cohort. Ninety patients from the main cohort had available MGMT methylation status, which comprised of 32 females (12 methylated and 20 unmethylated) and 58 males (18 methylated and 40 unmethylated).…”
Section: Mgmt Methylationmentioning
confidence: 99%